2016
DOI: 10.21037/asvide.2016.312
|View full text |Cite
|
Sign up to set email alerts
|

Management of type A dissection with malperfusion

Abstract: Malperfusion is a common lethal complication of acute aortic dissection following rupture, for which the optimal management strategy has yet to be clearly established. The objective of this study was to reassess the management of acute type A aortic dissection (Type A-AAD) with malperfusion. We retrospectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In our series, the mortality rate was higher (17.5%), but we had a higher incidence of preoperative malperfusion syndrome, which is known to be a lethal complication for which the optimal management strategy has yet to be clearly established. 22 Yang and colleagues 23 recently showed their results in the delayed treatment of acute dissections after implantation of the stent in the true lumen. 23 Their results support the notion that the complication of malperfusion with end-organ dysfunction carries a high mortality risk irrespective of early reperfusion, stabilization, and delayed surgical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, the mortality rate was higher (17.5%), but we had a higher incidence of preoperative malperfusion syndrome, which is known to be a lethal complication for which the optimal management strategy has yet to be clearly established. 22 Yang and colleagues 23 recently showed their results in the delayed treatment of acute dissections after implantation of the stent in the true lumen. 23 Their results support the notion that the complication of malperfusion with end-organ dysfunction carries a high mortality risk irrespective of early reperfusion, stabilization, and delayed surgical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…22 Yang and colleagues 23 recently showed their results in the delayed treatment of acute dissections after implantation of the stent in the true lumen. 23 Their results support the notion that the complication of malperfusion with end-organ dysfunction carries a high mortality risk irrespective of early reperfusion, stabilization, and delayed surgical reconstruction. Visceral ischemia can go unnoticed because preoperative symptoms are often ambiguous and may become exacerbated without discernible symptoms during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large difference in mortality in looking at these 3 groups, with published rates demonstrating early mortality of ATAAD with class "a" of roughly 10% compared to patients with class b or c characteristics having mortality of 38% percent or higher. 8,9 This is an important distinction when comparing studies that look at mortality outcomes in ATAAD such as the current study by Jin et al in this month's issue of JCVA. 10 The authors retrospectively reported on 121 patients who underwent surgical repair for ATAAD with Penn class Aa dissections.…”
mentioning
confidence: 98%
“…Stenting or fenestration to restore flow into malperfused vital organs followed by delayed corrective surgery resulted in lower mortality than direct definitive treatment. [6][7][8] In a study by Uchida et al, in-hospital mortality of patients with TAAD complicated by a malperfusion syndrome who underwent surgery was five times greater than those without malperfusion syndrome. Early reperfusion before surgery was able to significantly lowered the mortality to similar levels of patients without malperfusion syndrome.…”
Section: Discussionmentioning
confidence: 99%